Peran media sosial sebagai penunjang akademik mahasiswa di era digital - Aulia, Nurul (Maliki Interdisciplinary Journal, 2024)
In this digital era, almost all people use social media, both children, teenagers, adults and even parents. Social media is a means of communication for everyone regardless of time or distance. Everything can be accessed from social media, both positive and negative things. Social media can have a positive impact if we use it for positive things. Likewise with students, in this digital era social media plays an important role as a support for academics. Students can use social media to interact, exchange ideas, seek information, and even create their own achievements.